Performance test of a half-feed peanut-cleaning picker suitable for clay hill areas in southern China - Wang, Shenying; You, Zhaoyan; Sun, Dawei; Xiao, Qiang; Luo, Qiaojun; He, Lin (International Journal of Agricultural and Biological Engineering, 2024)
To solve the problems of excessive soil lumps, broken branches and seedlings in pods and difficulty in removing impurities in the harvested pods of peanuts in the hilly areas of southern China, which is due to the high soil viscosity and easy hardening, and to improve the soil removal effect of the peanut half-feed pod picker in hilly areas of China, this article designed a half-feed peanut-cleaning picker suitable for southern clay hilly areas and provided a detailed introduction to the overall structure, working principle, and adjustment methods of various operating parameters. Through field measurement experiments, the influencing factors and laws of soil removal performance indicators, such as the comprehensive soil removal rate and POD drop rate, were studied. The results showed that the comprehensive soil removal rate gradually increased with increasing soil patting frequency, soil patting amplitude, and picking roller speed, first increased and then decreased with increasing picking roller gap and gradually decreased with increasing soil patting plate gap and clamping conveyor chain speed. The comprehensive soil removal rate of the soil patting plate using the opposite patting method was greater than that of the swinging patting method. The soil removal pod drop rate increased gradually with increasing soil patting frequency and amplitude and decreased with increasing soil patting plate gap and clamping conveyor chain speed. The soil removal pod drop rate of the soil patting plate using swing patting was lower than that using the opposite patting method. The speed and gap of the picking roller had no effect on the soil removal pod drop rate. The frequency, amplitude, form, and gap of the soil patting plate had extremely significant impacts on the rate of decrease in the number of soil removal pod drop rate. The clamping conveyor chain speed had a significant impact, while the speed and gap of the picking roller had no significant impact. The influence of all factors on the comprehensive soil removal rate was extremely significant. This study provides a theoretical basis and technical reference for parameter optimization research on peanut-cleaning picking machines in the clay hilly areas of southern China. Key words: peanut; southern clay hilly areas; picker; comprehensive soil removal rate; soil removal pod drop rateDOI: 10.25165/j.ijabe.20241704.8782Citation: Wang S Y, You Z Y, Sun D W, Xiao Q, Luo Q J, He L. Performance test of a half-feed peanut-cleaning picker suitable for clay hill areas in southern China. Int J Agric & Biol Eng, 2024; 17(4): 156–164.